Contribution to the genus Nicephora Bolívar, 1900 (Orthoptera: Tettigoniidae: Meconematinae) with one new species from Yunnan, China - Liu, Qing; Su, Jie; Shi, Fuming (Zootaxa, 2024)
This paper reports one new species of Nicephora Bolívar, 1900 from Yunnan, China, namely Nicephora acumina sp. nov., and gives a supplemental description of Nicephora (Eunicephora) dianxiensis Wang & Liu, 2013. Diagnostic illustrations are provided, and all specimens examined are deposited in the Museum of Hebei University, China.